2021
DOI: 10.1017/s0022215121003923
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of idiopathic benign paroxysmal positional vertigo subtype by hospital visit type: experience of a single tertiary referral centre

Abstract: Objective To investigate the incidence of benign paroxysmal positional vertigo subtype by hospital visit type (i.e. out-patient department vs emergency room), in a single tertiary referral centre. Methods A total of 772 consecutive patients with benign paroxysmal positional vertigo were included. Using head-roll and Dix–Hallpike tests, benign paroxysmal positional vertigo subtype was determined as canalolithiasis posterior semicircular canal benign paroxysmal positional vertigo, geotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Future work should focus on education and training of ED providers on appropriate application and interpretation of Dix–Hallpike test and treatment of BPPV. In addition, as providers become more familiar with pc‐BPPV and if subsequent data confirm recent studies suggesting that hc‐BPPV is more common in an early‐presenting population than previously thought, 3,61,181,182,237 learning about other variants, especially geotropic and apogeotropic hc‐BPPV, will allow correct management of a much larger proportion of BPPV patients (and thus, of all patients with acute dizziness).…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Future work should focus on education and training of ED providers on appropriate application and interpretation of Dix–Hallpike test and treatment of BPPV. In addition, as providers become more familiar with pc‐BPPV and if subsequent data confirm recent studies suggesting that hc‐BPPV is more common in an early‐presenting population than previously thought, 3,61,181,182,237 learning about other variants, especially geotropic and apogeotropic hc‐BPPV, will allow correct management of a much larger proportion of BPPV patients (and thus, of all patients with acute dizziness).…”
Section: Methodsmentioning
confidence: 70%
“…After a lengthy debate about hc‐BPPV, the writing committee made a conscious decision to simplify our recommendations and to restrict them to pc‐BPPV (the most common type). Some committee members felt that a recommendation for hc‐BPPV should have been included because this variant constitutes an important minority of total BPPV patients, especially in acutely presenting patients in an ED population, 237 because hc‐BPPV patients are often more severely symptomatic than patients with pc‐BPPV 238 …”
Section: Methodsmentioning
confidence: 99%
“…El diagnóstico de neuritis vestibular (VN) se dio a seis de las siete personas que fueron examinadas después Covid-19 (53). Se utilizó la prueba de Dix-Hallpike para determinar si el paciente experimentaba o no un episodio de (VPPB) (54). En relación con el tratamiento de disfunción eréctil, las opciones terapéuticas disponibles actualmente, por ejemplo, recomiendan un mayor tiempo dedicado al ejercicio, mantener una dieta equilibrada, consumir menos alcohol y drogas.…”
Section: Fuente: Elaborado Y Diseñada Por El Autorunclassified
“…We have recently reported that the incidence of BPPV subtypes differs according to the type of hospital visit, ie, whether the patient is evaluated at the outpatient department (OPD) vs emergency room (ER). 8 The coronavirus disease 2019 (COVID-19) pandemic has markedly impacted patient and provider lifestyles, including patterns of healthcare system use. During the severe crisis period, only emergency and oncology services were active in the tertiary referral medical center, as was the case in many other hospitals.…”
Section: Introductionmentioning
confidence: 99%